Factors that influence intention to quit among Pertama Crane & Engineering Sdn Bhd employees - Nurul Huda, Abdul Aziz (2020)
The intent to quit is a commonly studied phenomenon that influenced by various factors. This research focuses on analysing whether resilient, job satisfaction, and religiosity influence such intention to quit among employees at Pertama Crane & Engineering Sdn Bhd. The primary data was gathered using survey questionnaires distributed to targeted respondents. A total of 95 respondents have participated in this research. The unit of analysis are individual technical employees that include those mechanics, wiremen, crane operators, welders, low loaders and engineers which are considered as vulnerable to employee turnover. The collected data were then be analysed using SPSS version 24 in which Multiple Linear Regression was applied accordingly to test possible significant relationships among those selected independent variables and the dependent variable (intention to quit). Results of this research have indicated that job satisfaction and religiosity do affect the intention to quit. Though two hypotheses were significantly supported (job satisfaction and religiosity), variable of resilience is not significant in influencing intention to quit. It is suggested that to reduce intention to quit, managers need to actively monitor both extrinsic and intrinsic sources of job satisfaction among their employees. Other than that, providing flexible scheduling to accommodate employees' religious practices at workplace and taking religious holidays into account when planning work-related events is also essential. These activities could assist in maintaining and increasing job satisfaction and religiosity commitment towards the organisation. Discussion of main findings, implications of research, limitations and recommendations for future research are also highlighted at the end of this research project